Effect of Durian By-Product on Nutrition Intake, Productivity, and Physiological Conditions of Kacang Goats (Capra aegagrus hircus) - Padang; Sirajuddin Abdullah; Sagaf; Sri Wulan Cakrawati; Harmoko (Postgraduate, University of Mataram, 2023)
The native plant of mainland Asia, Durian, presents a considerable opportunity to be used as animal feed due to the high by-product production, with almost 70% of every durian fruit being waste. This presents an excellent opportunity to repurpose durian skin and seeds as animal feed. An experiment was conducted to evaluate the impact of durian by-product on the productivity and physiological condition of kacang goats. The research was conducted from September to November 2020 at the Experimental Cage owned by CV. Prima BREED, Palu City, Central Sulawesi Province. The research cages were stage cages, with a size of 2 x 10 m, and one animal was placed in each cage. A total of 18 Peanut goats were divided into 3 treatment levels and 6 replications according to a completely randomized design. The study found that the nutritional intake of durian by-product in the form of rind and seed flour as much as 0.5% in the feed affected the carcass percentage, the amount of red blood cell, hemoglobin level, and hematocrit value but had no effect on body weight gain, dry matter consumption, feed use efficiency, carcass weight, weight and percentage of non-edible carcasses, body temperature, respiration frequency, pulse frequency, and white blood cell count of kacang goats. This indicates that the utilization of 0.5% durian by-product (seeds and rind) in feed did not have a negative effect on the productivity and physiological condition of kacang goats, making it a viable option for animal feed.